Economic Growth, Unemployment, and Human Development on Poverty in North Sumatra Province in 2011-2020 - Juni Florida Sirait; Tri Haryanto (MediaTrend, 2022)
National development that is running in Indonesia is expected to create an evendistribution of welfare so that no one is left behind and experiences poverty.However, the fact is that the development only touches the interests of certaingroups and the results can only be enjoyed by a few people. This study aims toanalyze the effect of economic growth, unemployment and human development on poverty levels in North Sumatra during 2011-2020. The analytical method usedin this research is panel data regression with Random Effect Model (REM). Theresults showed that economic growth and human development had a negative andsignificant impact on poverty in North Sumatra Province. In contrast to the resultsfound in unemployment, this variable has no statistically significant effect onpoverty in this province. The results of this study are expected to be able to enrichreferences in reducing regional poverty levels. There is a need for governmentintervention to increase economic growth and human development. Increasingeconomic growth can be done by expanding job opportunities, especially during the current covid pandemic, while increasing human development can be intervened through education subsidies, and cheap health services, especially for the poor.